HUBUNGAN KEBIASAAN SARAPAN PAGI DENGAN KONSENTRASI BELAJAR SISWA SEKOLAH DASAR - Siti Hajar Wulandari; Edi Yuswantoro (Suluh Adiluhung Publisher (SAPub), 2026)
Breakfast habits play an important role in supporting children’s cognitive functions, particularly learning concentration. However, a number of elementary school students still do not have the habit of eating breakfast before attending school. This study aimed to analyze the relationship between breakfast habits and learning concentration among elementary school students at SDN 1 Wonorejo, Tulungagung Regency. This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 39 students in grades IV, V, and VI who were selected using purposive sampling. Data on breakfast habits were collected using a structured questionnaire, while learning concentration was measured using the Grid Concentration Test (GCT). Data were analyzed using the Spearman rank correlation test. The results showed that most students had good breakfast habits (64%) and a moderate level of learning concentration (72%). Statistical analysis revealed a significant relationship between breakfast habits and learning concentration (p-value = 0.000; p < 0.05). These findings indicate that good breakfast habits are significantly associated with better learning concentration among elementary school students. Therefore, promoting regular breakfast consumption is essential to support optimal learning concentration in school-aged children.